Made in China versus Made in Spain. A corpus-based study comparing AD in Chinese and Spanish - Yuchen Liu; Helena Casas-Tost; Sara Rovira-Esteva (JoSTrans: The Journal of Specialised Translation)
This article presents a corpus-based study comparing AD in Chinese and Spanish, as a first step towards testing the feasibility of AD translation from Spanish into Chinese. A bilingual multimodal corpus consisting of eight films with AD in both languages was first compiled, and then a labelling scheme was designed for the corpus annotation with ATLAS.ti. The results from a quantitative and qualitative analysis of this corpus show that there are many similarities in content selection between Chinese and Spanish AD, which justifies our proposal of translating AD scripts from Spanish into Chinese to increase AD in China. However, we also found that Chinese AD carries a higher information load than Spanish AD. There are also differences in the general approach to AD, in the sense that Chinese scriptwriters tend to intervene or interpret more than their Spanish counterparts. Therefore, such differences also suggest the need for a certain degree of localisation if AD is translated from Spanish into Chinese instead of created ex novo.